A Narrative Review on Efficacy and Safety of Proton Pump Inhibitors in Children - Dipasquale, Valeria; Cicala, Giuseppe; Spina, Edoardo; Romano, Claudio (Frontiers in Pharmacology, 2022)
Proton pump inhibitors (PPIs) are among the most prescribed drugs worldwide and include omeprazole, esomeprazole, lansoprazole, pantoprazole, and rabeprazole. Their use in pediatrics is approved for children older than 1 year, for the short-term treatment of symptomatic gastroesophageal reflux disease (GERD), healing of erosive esophagitis, treatment of peptic ulcer disease, and eradication of Helicobacter pylori. PPIs are also considered the standard of care for pediatric eosinophilic esophagitis. Despite the strict range of indications, the use of this class of molecules has increased in all pediatric age ranges. The long-term gastric acid suppression in children has been linked to increased risks of gastrointestinal and lower respiratory tract infections, bone fractures, and allergy. This study aims to provide a comprehensive overview of the mechanism of actions, use (and misuse) in infants and children, and safety of PPIs.